Bauran Promosi Film Bioskop di Instagram - Tiara Jasmine; Anne Ratnasari (Bandung Conference Series: Public Relations, 2023)
Abstract. Technological developments are increasing well and quickly, such as in the world of cinema film entertainment through Instagram social media. Companies must improve their marketing better in order to achieve their goals and make promotions more attractive in every content they create. Rhaya Flicks also creates creative content such as information conveyed through photos or graphics and creative content such as Script to screen through a video about the film, Qodrat, which is then uploaded to Instagram with a detailed design so that the message conveyed will also reach Rhaya Flicks' target consumers. . Rhaya Flicks is engaged in agency or marketing which focuses on cinema films. The purpose of this study was to analyze the presentation of Qodrat film advertisements through Instagram social media, Qodrat film sales promotion on Instagram, what obstacles were passed in managing the Qodrat film promotion and what efforts were made to overcome them as well as the use of script to screen content to attract the attention of moviegoers. This study uses a qualitative research method with a case study approach. Data collection techniques in this study were carried out using interviews and observation techniques. And the subject of this research is the marketing division, creative director and Instagram admin @Qodrat.movie by Rhaya Flicks and also followers from @qodrat.movie. This research resulted in strategic steps for developing marketing in the film sector so that there would be references for groups of people who were interested in developing their potential and looking for opportunities in the field of cinema film promotion and even existing film agency companies. Abstrak. Perkembalngaln teknologi semalkin meningkalt dengan baik dan cepat seperti pada dunia hiburan perfilman bioskop melalui media sosial Istagram. Perusahaan harus meningkatkan pemasarannya dengan lebih baik agar mencapai tujuan dan membuat promosi yang lebih menarik di setiap konten yang dibuat. Rhaya Flicks juga membuat konten kreatif seperti informasi yang disampaikan melalui foto atau grafis dan konten kreatif seperti Script to screen melalui video mengenai film tersebut yaitu Qodrat lalu di unggah ke Instagram dengan desain yang detail sehingga pesan yang disampakan juga akan sampai kepada sasaran konsumen perusahaan Rhaya Flicks. Rhaya Flicks bergerak di bidang agency atau marketing yang fokus pada film bioskop. Tujuan penelitian ini untuk menganalisis penyajian iklan film Qodrat melalui sosial media Instagram, sales promotion film Qodrat di Instagram, hambatan apa saja yang dilalui dalam pengelolaan promosi film Qodrat dan apa upaya untuk mengatasinya serta penggunaan konten script to screen untuk menarik perhatian penonton bioskop. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data dalam penelitian ini dilakukan menggunakan teknik wawanacacra dan observasi. Dan subjek penelitian ini adalah divisi marketing, creative director dan admin instagram @Qodrat.movie oleh Rhaya Flicks dan juga followers dari @qodrat.movie. Penelitian ini menghasilkan langkah-langkah strategis pengembangan marketing di bidang film sehingga akan ada rujukan bagi kelompok masyarakat yang berminat dan mengembangkan potensi dan mencari peluang dalam bidang promosi film bioskop bahkan perusahaan agency film yang sudah ada.